Surveillance of HIV-1 Antiretroviral Drug Resistant Strains in Thailand in 2010 - เกาะเรียนอุดม สุรพล (Disease Control Journal, 2011)
In this study, surveillance of HIV-1 antiretrovral drug resistance was conducted on 493 cases ofboth AIDS/HIV infected patients who received ARV drug treatment for more than 6 months and also ARVna?ve patients from 18 provinces in all parts of Thailand. Most of patients recieving ARV were treated with GPO-VIR (49.0%). All plasma samples of 493 patients were assessed for viral load level and 7 ARV treated patients and 160 ARV-naïve patients had viral load > 1,000 copies/ml that were further analyzed for HIV-1 antiretrovral drug resistance by genotyping assay. In ARV treated group, NRTI drug resistant mutation that associated with resistance to 3TC (and FTC) was found in 4 of 6 patients who having HIV drug resistance. For NNRTI drug resistance, resistance to NVP and EFV were found in 6 and 2 patients respectively.PIs-associated mutations were also found in all 8 ARV treated patients but no one was resistant to PIs. In ARV-naive group, no NRTI drug resistance was found in all 8 patients but 5 patients showed NNRTI drug resistance with resistance to NVP and EFV in 5 and 2 patients respectively. PIs-associated mutations were also found in 3 ARV-na?ve patients with resistant to IDV and APV/FPV. In conclusion, the percentage of ARV drug (NRTIs and/or NNRTIs) resistance was 2.0% (6/292) in ARV treated group, with maximum rate of 3.4% (2/58) in patients treated for more than 6 month to 1 year. In ARV-na?ve group, however, 4.3% (8/183) of ARV drug (NNRTIs or PIs) resistance were found. The overall rate of HIV drug resistance in all AIDS/HIV infected patients was 2.9% (14/475) in this study.